Recalling the Belgian Congo : conversations and introspection - Dembour, Marie-Bénédicte, 1961- (New directions in anthropology, 2000)
When the author embarked on her study, her aim was to approach former colonial officers with a view to analyzing processes of domination in the ex-Belgian Congo. However, after establishing a rapport with some of these officers, the author was soon forced to revise her initial assumptions, widely held in present-day Belgium: these officers were not the ""baddies"" she had expected to meet. Exploring the colonial experience through the respondents' memories resulted in a far more complex picture of the colonial situation than she had anticipated, again forcing her to question her origi.